Trehalose accumulation of strains of Saccharomyces during alcoholic fermentation - Gutierrez, L.E. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1990)
This study was carried out to compare the effects of several factors (temperature, pH, sucrose concentration, 2,4-dinitrophenol and nitrogen sources) on trehalose production by Saccharomyces uvarum IZ-1904 and Saccharomyces cerevisiae (M-300-A and baker's yeast) during alcoholic fermentation. Trehalose production was lower with the yeast LZ-1904 than with M-300-A or baker's yeast. More trehalose was formed at 34°C than at 25°C. For M-300-A and baker's yeast trehalose accumulation was higher at pH 4.5 than at pH 3.0. Addition of 18ppm 2.4-dinitrophenol strongly decreased the amount of trehalose formed by baker's yeast, but was ineffective for IZ-1904. Increase of sucrose concentration led to a higher production of trehalose.